Penyelesaian Sengketa Tanah Oleh Kepala Desa Sebagai Mediator (International Forum of Researchers and Lecturers, 2023)
This research aims to find out and explain the resolution of land disputes by the village head as a mediator. This type of research uses research, with descriptive research characteristics. The research location is Polanharjo Police, Klaten Regency. This research uses a qualitative research method which aims to explain a phenomenon in depth. This research also uses a socio-juridical approach, namely an approach that studies the extent to which symptoms or phenomena in society can influence existing laws or regulations. The analysis technique is carried out descriptively. The results of this research are that the important role of the village head is needed to resolve land disputes in his area, this is because the village head is an instrument of the village government which is obliged to participate in resolving disputes between the community.